Enhancing the Transfer of Life Skills from Sport-based Youth Development Programs to School, Family, and Community Settings - Jacobs, Jennifer M; Lawson, Michael; Ivy, Victoria Nicole; Richards, K. Andrew R. (Journal of Amateur Sport, 2017)
When designed intentionally, sport-based youth development programs engage youth in physical activity, sport, and exercise as a way to concurrently pursue goals related to socioemotional and physical development (Holt et al., 2017). One such application of this is the Teaching Personal and Social Responsibility (TPSR) model (Hellison, 2011) which has the ultimate goal of students transferring lessons learned within the sport setting to other areas of their life, including family, community, and school. However, once youth leave the program setting, they become vulnerable to challenges from external systems working to support or hinder their transfer of life skills (Martinek & Lee, 2012). Therefore, we propose that (in)congruence among family, school, community and program systems influence the extent to which lessons learned can transfer to other areas of their lives. Specifically drawing from the frameworks of Collective Parental Engagement (Alameda-Lawson & Lawson, 2016) and Students Multiple Worlds’ model (Phelan, Davidson, & Cao, 1991), we argue that skills and competency transfer is best facilitated when social settings which comprise youth’s social systems share similar values and expectations for desired behavior. Practical strategies for enhancing the transferability of lessons learned in TPSR programs through the congruence approach are shared.